Maternal palmitic acid intake, palmitic acid levels in maternal blood and cord blood with infant body composition - Amira Ayu Aronasty; Mira Dewi; Ali Khomsan (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2024)
The fat intake of pregnant mothers, especially palmitic acid, which is one of the main components of palm oil, may affect the weight and fat mass of newborns. This study aimed to analyze the relationship between maternal palmitic acid intake and palmitic acid levels in maternal and cord blood with birth weight and infant fat mass. This study uses secondary data using a cross-sectional design, which is part of the main study of the BSEA and IPB University. The research was conducted from May to October 2018 at the Tanah Sareal Health Center and North Bogor Health Center. A total of 142 pregnant women were selected based on a single pregnancy and Hb level of >9 mg/dL. Exclusion criteria were the presence of congenital abnormalities or undergoing therapy for a particular disease. Data analysis was performed using the Pearson/Spearman correlation test. The results of the study showed no association between maternal palmitic acid intake and birth weight or infant fat mass (p> 0,05). Two approximate significant indicators were palmitic acid level in maternal blood with birth weight (p= 0,089), as well as palmitic acid level in cord blood with infant fat mass (p= 0,053). In conclusion, maternal palmitic acid intake and palmitic acid levels in maternal and cord blood did not affect birth weight or infant fat mass.